Structural behaviour of pre-fabricated composite pad footing foundation using cold-formed steel of lipped channel sections - Koo, Ting Choong, author; Mahmood Md. Tahir, 1962- , supervisor; Shek, Poi Ngian, 1982- , supervisor; Fakulti Kejuruteraan Awam (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Kejuruteraan (Struktur)) - Universiti Teknologi Malaysia, 2017